1986
DOI: 10.1016/0014-5793(86)81027-4
|View full text |Cite
|
Sign up to set email alerts
|

Neo‐kyotorphin, an analgesic peptide isolated from human lung carcinoma

Abstract: A pentapeptide with analgesic activity has been isolated from human lung squamous cell carcinoma and from three other types of propagated tumors of human lung small-cell carcinoma (SCC), adenoma (AD) and large-cell carcinoma (LCC) in nude mice. The amino acid sequence of the peptide has been revealed to be H-Thr-Ser-Lys-Tyr-Arg-OH, which is exactly the same as that of neo-kyotorphin, an analgesic peptide originally isolated from bovine brain [(1982) Life Sci. 31, 17331. No neo-kyotorphin could be isolated from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1997
1997
2000
2000

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…In contrast to neokyotorphin, its fragment induces cytolysis of tumor cells [21, 39]. The presence of high amounts of neokyotorphin in lung carcinoma suggests its involvement in tumor development [40]. It was recently found that two groups of α‐globin fragments, (1–32)‐(1–30) and (106–141)‐(110–141), induce a 30–60% increase of proliferative tumor cell growth [41].…”
Section: Biological Activities Of the Components Of Tissue‐specific Pmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to neokyotorphin, its fragment induces cytolysis of tumor cells [21, 39]. The presence of high amounts of neokyotorphin in lung carcinoma suggests its involvement in tumor development [40]. It was recently found that two groups of α‐globin fragments, (1–32)‐(1–30) and (106–141)‐(110–141), induce a 30–60% increase of proliferative tumor cell growth [41].…”
Section: Biological Activities Of the Components Of Tissue‐specific Pmentioning
confidence: 99%
“…Accordingly, several pathologies are accompanied by changes in composition and content of the fragments of functional protein in tissues [14–18, 28, 40, 41]. Notwithstanding the clinical and biochemical differences, these pathologies have a common principal feature – they involve alterations in tissue homeostasis or metabolic state of the cells, independently of the nature of the disease: cell transformation [40, 41], tissue atrophy (Alzheimer's disease and ischemia [16–18]) or impaired lymphoproliferation (Hodgkin's disease [28]). Activity of the components of tissue‐specific peptide pools in cell cultures in vitro shows that their biological role might be due to prevention of tumor cell growth or to control of viability, growth and differentiation of cells of the tissues, i.e.…”
Section: Tissue‐specific Peptide Pools As a Novel System Of Peptidergmentioning
confidence: 99%
“…However, significant changes in the composition and the content of peptide components of brain were shown to accompany the pathologies associated with alterations of brain metabolism, such as Alzheimer's disease [3] and brain ischemia [8]. Changes in the levels of haemoglobin fragments were detected in human erythrocytes for Hodgkin's disease [9] and lymphosarcoma [10], and in lung tissue during lung carcinoma [11]. Levels of haemoglobin-derived peptides were shown to increase in human blood plasma of donors subjected to physical exercise [12].…”
Section: Introductionmentioning
confidence: 99%
“…Since the findings of Brantl et al, systematic studies of peptide composition of various tissue extracts resulted in a great number of new peptides with structure mainly originating from α‐ or β‐globin chains [2]. In addition, some of these hemoglobin‐derived peptides were often found to coexist with various pathologies such as human lung adenocarcinoma [4], Alzheimer's disease [5], Hodgkin's disease [6]and brain ischemia [7]and even subsequently to physical exercise like long distance running [8]. In the latter study, it was noteworthy that the plasma level of the released hemorphin‐7 exceeded that of β‐endorphins by a factor of about 1000.…”
Section: Introductionmentioning
confidence: 99%